Integration of clinical parameters and CT-based radiomics improves machine learning assisted subtyping of primary hyperaldosteronism - Mansour, Nabeel; Mittermeier, Andreas; Walter, Roman; Schachtner, Balthasar; Rudolph, Jan; Erber, Bernd; Schmidt, Vanessa F.; Heinrich, Daniel; Bruedgam, Denise; Tschaidse, Lea; Nowotny, Hanna; Bidlingmaier, Martin; et al. (Frontiers in Endocrinology, 2023)
All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards. Data collection was according to the protocol of the German Conn's Registry approved by the Ethics Committee of the Medical Faculty of the Ludwig Maximilians University of Munich. Informed consent: All patients gave written informed consent, and the protocol of the German Conn's Registry was approved by the Ethics Committee of the University of Munich.